Design, fabrication and characterization of composite piezoelectric ultrafine fibers for cochlear stimulation. (15th May 2017) - Mota, Carlos; Labardi, Massimiliano; Trombi, Luisa; Astolfi, Laura; D'Acunto, Mario; Puppi, Dario; Gallone, Giuseppe; Chiellini, Federica; Berrettini, Stefano; Bruschini, Luca; Danti, Serena
Abstract: Sensorineural hearing loss, primed by dysfunction or death of hair cells in the cochlea, is the main cause of severe or profound deafness. Piezoelectric materials work similarly to hair cells, namely, as mechano-electrical transducers. Polyvinylidene fluoride (PVDF) films have demonstrated potential to replace the hair cell function, but the obtained piezoresponse was insufficient to stimulate effectively the auditory neurons. In this study, we reported on piezoelectric nanocomposites based on ultrafine PVDF fibers and barium titanate nanoparticles (BTNPs), as a strategy to improve the PVDF performance for this application. BTNP/PVDF fiber meshes were produced via rotating-disk electrospinning, up to 20/80 weight composition. The BTNP/PVDF fibers showed diameters ranging in 0.160–1.325 μm. Increasing collector velocity to 3000 rpm improved fiber alignment. The piezoelectric β phase of PVDF was well expressed following fabrication and the piezoelectric coefficients increased according to the BTNP weight ratio. The BTNP/PVDF fibers were not cytotoxic towards cochlear epithelial cells. Neural-like cells adhered to the composite fibers and, upon mechanical stimulation, showed enhanced viability. Using BTNP filler for PVDF matrices, in the form of aligned ultrafine fibers, increased the piezoresponse of PVDF transducers and favored neural cell contact. Piezoelectric nanostructured composites might find application in next generation cochlear implants. Graphical abstract: Highlights: A method was designed to increase sensitivity and performance of piezoelectrodes for cochlear stimulation. Ceramic/polymer composites were used to increase piezoelectric properties, anisotropic fibers to enhance the neurite/material interaction. Fiber alignment increased with tangential velocity of the collector, but fiber diameter was not affected. The piezoelectric coefficients proportionally increased with barium titanate weight percentage in the composites. The fibers were cytompatible and, under dynamic culture, enhanced the viability of neural cells.